INFLUENCE OF THE CAST IRON’S CHEMICAL COMPOSITION ON THE INTERPHASE DISTRIBUTION OF CR AFTER ANNEALING AT 690 °C - Netrebko, V. V.; Volchok, I. P. (Science and Transport Progress, 2017)
Purpose. The article is aimed to determine effect of the chemical composition of Fe-C-Cr-Mn-Ni cast iron on the chromium content in the metallic base, carbides and the coefficient of interphase distribution of chromium after annealing at 690 ° С (КРСr690). Methodology. Cast irons containing 1.09–3.91% C; 11.43–25.57% Cr; 0.6–5.4% Mn; 0.19–3.01% Ni and 0.8–1.2% Si were investigated. The analysis of chromium distribution was carried out using mathematical statistics methods. Cast iron was melted in induction furnace with a capacity of 60 kg. Findings. The use of methods of active planning of the experiment 24-1 allowed us to establish regression dependencies of the chromium concentration in the base and carbides, as well as its interphase distribution coefficient on the С, Mn, Cr and Ni content in the cast iron. Chromium, after annealing, was mainly concentrated in carbides. The chromium content of the base varies from 3.94% at 3.23% C, 5.4% Mn, 11.43% Cr and 3.01% Ni to 17.43% at 1.09% C, 0.60% Mn, 25.57% Cr and 1.32% Ni. The minimum value of the distribution coefficient of CRC690 was 2.1 in cast iron, of composition 1.09% C, 0.6% Mn, 11.43% Cr and 0.19% Ni, maximum 9.4 at 3.91% C, 0, 6% Mn, 11.43% Cr and 3.01% Ni. The distribution of chromium was determined by the amount and type of carbides formed. During annealing, the carbides’ composition was formed as a result of carbide-forming elements contention and replacement of iron and manganese atoms by chromium atoms. Originality. Authors obtained regression dependences of the chromium content in the base, carbides and its interfacial distribution coefficient on the chemical composition of Fe-C-Cr-Mn-Ni cast iron after annealing at 690 ° C. Practical value. The obtained dependencies allow predicting the chromium content in the metallic base and may be used during the elaboration of the new wear resistant cast irons compositions, as well as in the choice of heat treatment regimes.